SUNGAI MEANDER LUK ULO ANTARA KONDISI IDEAL DAN KENYATAAN - Nur, Arief Mustofa (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2014)
Luk Ulo River is the biggest river across Kebumen, Central Java. It crossKarangsambung Area in meander form. Meander River has a sinuosity index >1.5. Thatâ€™s why, its need to be proven if Luk Ulo River is a meandering river. Thisstudy start with measuring Indonesiaâ€™s Map which according to a theory aboutMeander River of Dury (1969) and field study. There are seven segments reveal abend which resemble the letter "S" and being measured also observation. Onlyfour segments are meanders, i.e. Kalikayen Pucangan, Pesanggrahan,Kedungwaru and Seling. Based on stadia study, Luk Ulo River inKarangsambung Area is classified as â€œmature-oldâ€ stadia. A riverâ€™s bend isaffected by lithology and geological structure which reflected in geologicalstraightness appearance.